Mobile Learning as a New E-Learning Strategy - Yousef A.Baker, El-Ebiary; Najeeb Abbas, Al-Sammarraie; Ban Salman, Shukur (2018)
Mobile learning (M-learning) entails e-learning method. As a new phase of distance learning, M-learning assists the distance learning environment, decreasing the confines of the customary education. The present study discusses the presently employed devices and tech-niques for the accomplishment of the mobile learning target. It is concluded in this study that the use of wireless apparatus in Wi-Fi envi-ronment will consistently increase the desire to employ M-Learning technology.